Knee osteoarthritis is associated with previous meniscus and anterior cruciate ligament surgery among elite college American football athletes - Smith, M. V.; Nepple, J. J.; Wright, R. W.; Matava, M. J.; Brophy, R. H. (Sports Health: A Multidisciplinary Approach, 2017)
Background: Football puts athletes at risk for knee injuries such meniscus and anterior cruciate ligament (ACL) tears, which are associated with the development of osteoarthritis (OA). Previous knee surgery, player position, and body mass index (BMI) may be associated with knee OA. Hypothesis: In elite football players undergoing knee magnetic resonance imaging at the National Football League`s Invitational Combine, the prevalence of knee OA is associated with previous knee surgery and BMI. Study Design: Retrospective cohort. Level of Evidence: Level 4. Methods: A retrospective review was performed of all participants of the National Football League Combine from 2005 to 2009 who underwent magnetic resonance imaging of the knee because of prior knee injury, surgery, or knee-related symptoms or concerning examination findings. Imaging studies were reviewed for evidence of OA. History of previous knee surgery—including ACL reconstruction, meniscal procedures, and articular cartilage surgery—and position were recorded for each athlete. BMI was calculated based on height and weight. Results: There was a higher prevalence of OA in knees with a history of previous knee surgery (23% vs 4.0%, P < 0.001). The prevalence of knee OA was 4.0% in those without previous knee surgery, 11% in those with a history of meniscus repair, 24% of those with a history of ACL reconstruction, and 27% of those with a history of partial meniscectomy. Among knees with a previous ACL reconstruction, the rate of OA doubled in tibiofemoral compartments in which meniscal surgery was performed. BMI >30 kg/m2 was also associated with a higher risk of OA (P = 0.007) but player position was not associated with knee OA. Conclusions: Previous knee surgery, particularly ACL reconstruction and partial meniscectomy, and elevated BMI are associated with knee OA in elite football players. Future research should investigate ways to minimize the risk of OA after knee surgery in these athletes. Clinical Relevance: Treatment of knee injuries in football athletes should consider chondroprotection, including meniscal preservation and cartilage repair, when possible